Effect of temperature in the degradation of cannabinoids: From a brief residence in the gas chromatography inlet port to a longer period in thermal treatments - García-Valverde, María Teresa; Sánchez-Carnerero Callado, Carolina; Díaz-Liñán, Maríadel Carmen; Sánchez de Medina, Verónica; Hidalgo-García, Jesús; Nadal, Xavier; Hanuš, Lumír; Ferreiro-Vera, Carlos (Frontiers in Chemistry, 2022)
The substantial increase in legalization and subsequent regulation of Cannabis has intensified the control and analytical monitoring of Cannabis products to assure the sample quality as well as to control the cannabinoid content of the crop. In this sense, the restriction to cultivate legal Cannabis plants has been limited to 0.2-0.3% of Δ9-THC content, depending on the host country laws. Thereby, Cannabis flowers containing more than this limit are considered illicit drug-type cultivations and requires the obtention of specific permits to work with them. The official method established by the European Commission set gas chromatography/flame ionization detector (GC-FID) as the proper instrument to analyse the delta-9 tetrahydrocannabinol (Δ9-THC) content. In the present work, the potential drawbacks associated to the utilization of the official method for the evaluation of the Δ9-THC content are described. Thus, the effect of the GC injector port temperature in the degradation of cannabinoids was evaluated, observing the degradation of CBD in a 20% generating Δ9-THC and CBN as by-products. Likewise, the 17.2% of Δ9-THC was degraded producing CBN. Therefore, although the brief residence of cannabinoids in the GC inlet, the effect of temperature is noteworthy and must be considered. Derivatization of cannabinoids should be a mandatory step to prevent the thermal degradation of cannabinoids, assuring the accuracy of the results. Furthermore, the evaluation of cannabinoids degradation thermally treated for longer periods of time was carried out. The kinetic degradation of CBD was evaluated in this way, observing a degradation of 0.22 µg/L per second. At the same time, the kinetic of appearance of Δ9-THC demonstrates the intermediate nature of this cannabinoid, being degraded at 0.03 s-1 · µM-1. The degradation of CBD also produced CBN and CBE as by-products.